DEVELOPING ENGLISH MORPHOLOGY MATERIALS FOR UNDERGRADUATE STUDENTS AT ALAUDDIN STATE ISLAMIC UNIVERSITY OF MAKASSAR - Sukirman Sukirman (ETERNAL (English, Teaching, Learning and Research Journal), 2015)
The objective of this study was to develop a textbook of English morphology materials. The data was obtained by interviewing the lecturer, analyzing the syllabus used at the university, validating the product to the two experts in English morphology, trying out the product to the users. The data was analyzed qualitatively and descriptively. Furthermore, ten aspects of the product were validated to the experts and tried out the users. The aspects were organization of the materials, instructional objectives, examples, exercises, activities, instruction, coverage of the materials, contents of the materials, language, and summaries. The findings of the try-out indicated that all the aspects were clear, understandable, and not confusing for the students. Also, the product was well-designed and attractive. They were also not too easy and difficult. In addition, they dealt with the objective of the course.